Likomba Kamerun Bananen Gesellschaft Aktiengeselschaft – Lease of Land at Likomba near Tiko (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial handing over notes on Likomba Kamerun Bananen Gesellschaft Aktiengeselschaft
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Handover Note; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies